PENGARUH TAX MINIMIZATION, TUNNELING INCENTIVE, DAN KEPEMILIKAN ASING TERHADAP TRANSFER PRICING - Firdila Rya; Zirman Zirman; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to test empirically : 1) the influence of tax minimization 2) tunneling incentive and 3) foreign ownership toward transfer pricing decision. Which consists of three independent variables, tax minimization (X1), tunnelimg incentive (X2), and foreign ownership (X3) with the dependent variable of transfer pricing (Y). This research uses sample of basic and chemical sector companies during 2015-2018 by using purposive sampling method. The used data is obtained from annual report of basic and mining sector companies listed in BEI. Sample method using purposive sampling method. Data analysis techniques used include descriptive statistics, data normality test, classical assumption test and hypothesis testing with linear regression. The result of this research on significance indicate that tax minimization (sig 0,002), and tunneling imcemtive (sig 0,028) effect on transfer pricing. This is shown in the test result that the significance calue of the variable is smaller than (<) 0,05. While and foreign ownership variable (sig 0,147) has no effect on transfer pricing. This is shown in the test result that the significance value of the variable is greater than (>) 0,05.Keywords : Tax Minimization, Tunnelimg Incentive, Foreign Ownership, Transfer Pricing